Impact of Music Therapy on the Emotional and Cognitive Development of Young Musicians - OLALLA , VERÓNICA ARROYO (Journal of Ecohumanism, 2024)
A systematic review was carried out on the production and publication of research papers related to the study of ICT, Student Competencies, Higher Education and Vocational Training under the PRISMA (Preferred Reporting Items for Systematic reviews and Meta-Analyses) approach. The purpose of the analysis proposed in this document was to know the main characteristics of the publications registered in the Scopus and Wos databases during the study of the proposed variables, achieving the identification of 62 publications in total. Thanks to this first identification, it was possible to refine the results through the keywords entered in the search button of both platforms, which were MUSIC THERAPY, EMOTIONAL DEVELOPMENT, COGNITIVE DEVELOPMENT, MUSICIANS, reaching a total of 16 documents, excluding duplicates and those that did not meet the analysis criteria. Among the main contributions, it is found that research in music therapy has also underlined its positive impact on social and emotional well-being, facilitating inclusion and social cohesion in group contexts, such as intergenerational choirs and educational programs. This shows that music therapy not only supports individual well-being, but also promotes healthier and more collaborative social interactions between different generations and groups.